Toponymical Suffixes of the Toponyms of Isfahan Province - TAGHVAEI, ELAHEH (Bulletin of Yerevan University B: Philology, 2021)
The most widespread and viable method of word-composition of the toponyms of Isfahan is suffixation by means of toponymic suffixes. However, the list of suffixes that make up the toponym in Isfahan is rather limited: -ābād, -ān, -gerd / -jerd, - vān. The article deals with compilations with the indicated toponymic suffixes.
Keywords: Iran, toponymy, Esfahan, toponymical suffixes, semantics